2015
DOI: 10.5230/jgc.2015.15.3.167
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Anastomotic Leakage: A Retrospective Cohort Study in a Single Gastric Surgical Unit

Abstract: PurposeAlthough several studies report risk factors for anastomotic leakage after gastrectomy for gastric cancer, they have yielded conflicting results. The present retrospective cohort study was performed to identify risk factors that are consistently associated with anastomotic leakage after gastrectomy for stomach cancer.Materials and MethodsAll consecutive patients who underwent gastrectomy at a single gastric surgical unit between May 2003 and December 2012 were identified retrospectively. The association… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
65
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(69 citation statements)
references
References 40 publications
4
65
0
Order By: Relevance
“…Many studies have indicated that EJ stricture and leakage after TG are closely related to the method of EJ . The results of the present study showed that the incidence of EJ‐related complications in the SETE group was lower than that in the ETS group, and the rate of EJ stricture was lower in the SETE group.…”
Section: Discussionsupporting
confidence: 44%
See 1 more Smart Citation
“…Many studies have indicated that EJ stricture and leakage after TG are closely related to the method of EJ . The results of the present study showed that the incidence of EJ‐related complications in the SETE group was lower than that in the ETS group, and the rate of EJ stricture was lower in the SETE group.…”
Section: Discussionsupporting
confidence: 44%
“…Many studies have indicated that EJ stricture and leakage after TG are closely related to the method of EJ. 12,13,39,40 The results of the present study showed that the incidence of EJ-related complications in the SETE group was lower than that in the ETS group, and the rate of EJ stricture was lower in the SETE group. For the ETS procedure, first, the anastomosis channel and the food channel were not consistent, and the diameter of the circular stapler was not exactly equal to that of the anastomotic stoma.…”
Section: Discussionmentioning
confidence: 43%
“…A total of seven articles fulfilled the selection criteria and were included in this systematic review (10)(11)(12)(13)(14)(15)(16). This pool of articles consisted of seven retrospective reports.…”
Section: Resultsmentioning
confidence: 99%
“…AL was found in 35 patients (6.7%). In the group of patients affected by leakage, the overall mean survival was significantly (13) included a total of 3,827 patients. They reported an AL rate of 1.88%.…”
Section: Resultsmentioning
confidence: 99%
“…Gastric fistula, a common complication in gastrointestinal surgery, usually occurs due to the failure of anastomotic healing in gastrointestinal anastomosis and reconstruction, or in the greater curvature of the stomach with a direct injury to the gastric wall followed by splenectomy. The incidence of gastric fistula and patient outcome are dependent on surgery type (1) and clinicopathological factors (2). According to a recent meta-analysis, the incidence and mortality rates following laparoscopic sleeve gastrectomy are ~2.2 and 0.11%, respectively (3), whereas the incidence is ~9.5% following gastrojejunostomy for the treatment of gastric carcinoma (4).…”
Section: Introductionmentioning
confidence: 99%